STUDI POTENSI DESA WISATA SIDOMULYO JEMBER SEBAGAI ALTERNATIF PEMBANGUNAN BERKELANJUTAN - faozen faozen; Hadi Jatmiko (Fakultas Pariwisata Universitas Pancasila, 2022)
The growth of the tourism sector has spurred various regions to compete to bring out tourism in their respective regions. Sidomulyo Village, Silo District, Jember Regency is a tourist village managed by the village community by optimizing its potential in the form of: natural tourism objects including Sendang Tirto Gumitir, a very clear and cool spring, the Pinus Raya Forest, all of which are still preserved, in this study focused on the development of sustainable tourism villages. This study aims to 1). Looking for alternative forms and approaches for rural tourism as an effort to realize sustainable tourism development, 2) Formulate a tourism management model that is socially, economically, and culturally sound for local communities in facing the era of globalization in the future. The data analysis used was descriptive and SWOT with a total sample of 18 community respondents, and 50 tourist respondents. The results showed (1) tourism potential; gaining the support of village regulations and policies; gaining the support of the community's acceptance and openness to tourists; the existence of a vision and mission; as well as public awareness of the importance of developing tourism potential, (2) tourism management is still very simple; lack of facilities, infrastructure and accessibility; limited number and quality of managers; lack of stakeholder engagement; as well as limited promotional activities, (3) government support for tourism development as an alternative to sustainable development in Jember Regency; the presence of special interest tourism development; tourist satisfaction and the desire to return to enjoy tourism in Jember is high; business diversification and increasing people's income; as well as support for technological developments, (4) the existence of illegal mines (dredging gumuk); the behavior of visitors/tourists who do not pay enough attention to environmental ethics; weak carrying capacity especially at the height of the holidays; public perception of the economic benefits of tourist villages; as well as competition between tourism objects, (5) The Potential Development of Sidomulyo Jember Tourism Village should establish a concentration strategy through horizontal integration or stability. Sidomulyo Jember Tourism Village implements a strategy that focuses on adding or improving natural tourism activities and educational tourism) Keywords: Tourism Village Potential, Community Empowerment, Sustainable Development)